THE HISTORY OF TURKISH WRITTEN LANGUAGE TAUGHT AT UNIVERSITY DEPARTMENT OF TURKISH LANGUAGE AND LITERATURE IN MACEDONIA WITH ROLEPLAYING (DRAMATIZATION) METHOD (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
This study describes 'The History of Turkish Written Language‘ with roleplaying (Dramatization) method in Macedonia, at University of Kiril and Methodius ' and “Goce Delchev” University in Stip at the Turkish Language and Literature Department. As it is known, using this method is much more than an artistic activity. But it is a way to support sustainability in mind in the education system. In this way, university students will see that Turkish language course is not consisted of just listening but also to be able to learn while having fun in the process of roleplaying (Dramatization). At the same time using these methods will cause increase of the mental skills at student interest in re-socialization and education of the Turkish section.Keywords: Macedonia, Turkish Language and Literature, Roleplaying (Dramatization), Turkish Language History.